(untitled) (Journal of the College of Education for Women, 2019)
Iraq has a range of small and large marshes, which can be divided into two groups, a group of marshes feeding water from the Tigris and Euphrates rivers, and a group of marshes fed by the seasonal valleys coming from the desert plateau and the aljazera plateau. The marshes have go through major changes, some of them turning into industrial lakes to store the flood waters of the Tigris and Euphrates rivers. Others have been dried up and turned into agricultural land. Others have dried up and the water has been returned to them in less quantities than before. The purpose of this research is to but light on the changes that have occurred in these marshes, with the mention of marshes turned into industrial lakes or agricultural lands in order to introduce the reader to these desolate marshes. And to highlighting the changes that have occurred in the marshes that have been coming from the Tigris and Euphrates rivers throughout history.